The association between parental postpartum depression and offspring autism spectrum disorder - Yin, Weiyao; Reichenberg, Abraham; Sandin, Sven; Silverman, Michael E. (Frontiers in Psychiatry, 2025)
ObjectivePostpartum depression (PPD) reportedly affects up to 20% of new mothers. While parental psychiatric history has been associated with an increased likelihood of neurodevelopmental conditions in the offspring, only a few studies of clinically diagnosed PPD exist exploring associated autism spectrum disorder (ASD) outcomes and no study to date has explored the contributions of paternal PPD with ASD risk or the combined influence.MethodsA nationwide prospective cohort of all live births in Sweden from 1997 through 2021, followed up through December 31, 2022. Associations between parental PPD and ASD were quantified by hazard ratios and two-sided 95% confidence intervals (CIs) from Cox regressions.ResultsAmong 1,781,349 live-births, ASD was diagnosed in 986 (4.6%) children of 21,461 born to mothers with PPD (574.3 per 100,000 person-years), 331 (5.3%) of 6,292 born to fathers with PPD (589.0 per 100,000 person-years), and 37 (8.8%) of 420 when both parents had PPD (1177.3 per 100,000 person-years). The hazard ratio of ASD when the mother was diagnosed with PPD was 2.56[CI:2.29-2.85], for fathers 2.59[CI:2.43-2.76] and both 5.54[CI:4.02-7.65]. Adjustment for possible confounders and depression history provided similar trends (mother 1.53[CI:1.36-1.71], fathers 1.71[CI:1.60-1.83] and both 2.19[CI:1.58-3.03]).ConclusionParental PPD was associated with an increased risk of ASD in the offspring, and this association was partially, though not fully, explained by depression history, antidepressant use, and other parental psychiatric factors. The magnitude of the association increased comparably when either parent was diagnosed with PPD and increased further when both parents were diagnosed, with a pattern indicative of shared genetic influences.